2021
DOI: 10.1371/journal.pone.0250014
|View full text |Cite
|
Sign up to set email alerts
|

What empowerment indicators are important for food consumption for women? Evidence from 5 sub-Sahara African countries

Abstract: This paper draws on data from five sub-Sahara African countries; Uganda, Rwanda, Malawi, Zambia, and Mozambique consisting of 10,041 married women who were cohabitating with a male spouse. The study aim was to investigate the relationship between women’s empowerment and women’s dietary diversity and consumption of different food items. Women’s empowerment was measured using the indicators in the five domains of Women’s Empowerment in Agriculture index (WEAI) and women’s dietary diversity and food consumption w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The influence of gender roles and empowerment on diets has been investigated in three studies ( 45 , 50 , 61 ). One study among women across five African countries explored the relationship between women's empowerment and the consumption of vegetables and combined FV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of gender roles and empowerment on diets has been investigated in three studies ( 45 , 50 , 61 ). One study among women across five African countries explored the relationship between women's empowerment and the consumption of vegetables and combined FV.…”
Section: Resultsmentioning
confidence: 99%
“…One study among women across five African countries explored the relationship between women's empowerment and the consumption of vegetables and combined FV. Results showed that women's autonomy and input in production decisions were positively associated with the consumption of dark green leafy vegetables, as well as with the consumption of vitamin A-rich FV, while leadership opportunities measured as “women are comfortable speaking in public” was associated only with combined FV consumption (e.g., other fruit and vegetables), but not with dark green leafy vegetables or combined FV (e.g., other vitamin A-rich FV) ( 61 ). In one study in urban Ethiopia, “husband's encouragement,” which was described as a social support within the household, was positively associated with women's combined FV consumption ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results also illustrated that intrinsic agency has a significant effect on families with low household wealth, while resources have a significant effect on families with high household wealth. Two studies utilizing the Demographic and Health Surveys (DHS) data in different countries found that improving intrinsic agency for women in low socioeconomic status was associated with better childhood nutrition [ 53 , 63 ]. Enabling resources, thus, tend to make a difference in women who belong to a higher wealth status, which could explain why the disparity between women and their husbands is larger in those of higher socioeconomic status compared to those of lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have found that a unit increase in empowerment scores across different domains is associated with increases in the probability of improved dietary diversity and nutrition outcomes (10,48,49) however, such associations might matter for a narrower list of food items. While Onah et al (13) using quantitative means found varied associations between empowerment domains and the consumption of specific food groups for women, this study goes further by qualitatively examining the socio-economic nuances that inform some of these varied quantitative associations.…”
Section: Discussionmentioning
confidence: 82%
“…Numerous studies have utilised the MDD-W measure to find a strong link between improved dietary diversity and health outcomes (6,(9)(10)(11) . Evidence also suggests that there are many determinants of improved dietary diversity for women with different contextual factors playing an important role in women's food consumption (9,12,13) .…”
mentioning
confidence: 99%